Investigating archery stance performance based on geometric morphometrics - Erliza, Erliza (Universiti Sains Malaysia, 2017)
Geometric morphometries (GMM) is a method to quantify the size and shape of organisms with the application of multivariate statistics. In this project, the participants’ archery stance was examined by landmark-based GMM analysis. The goal of this study was to correlate demographic factors of participants’ archery stance in related to score. The factors that had been explored in the study was age, height, weight, hand grip strength as well as back and leg strength. Two cameras were utilised to record video of 20 participants' archery stance and take picture of the target board, separately. Still screenshots images of participants' archery stance analysed using three available softwares: tpsUtil, tpsDig2 and MorphoJ. The result of this project suggests that GMM assessment of archery stance by hand grip strength as well as back and leg strength are more reliable indicator compared to score, age, height and weight. However, the level of significance is not really high at only 33.1% for hand grip strength and 23.1% for back and leg strength. The results from Principle Component Analysis suggest that the total variance of five axes: PC1, PC2, PC3, PC4 and PC5 summarises 84.7% of the observed shape variation. Therefore, it can be concluded that GMM can be utilised in archery studies as to provide better understanding and information on archery. It is recommended for other scholars or researchers to conduct a study of sport science by employing GMM as their method of analysis.